Unemployment in Latin America and the Caribbean (2011)
This study constructs a new data set on unemployment rates in Latin America and the Caribbean and then explores the determinants of unemployment. We compare different countries, finding that unemployment is influenced by the size of the rural population and that the effects of government regulations are generally weak. We also examine large, persistent increases in unemployment over time, finding that they are caused by contractions in aggregate demand. These demand contractions result from either disinflationary monetary policy or the defense of an exchange-rate peg in the face of capital flight. Our evidence supports hysteresis theories in which short-run changes in unemployment influence the natural rate.